Arterial hypertension and aortic root dilatation: an unsolved mystery - Alberto Milan; Francesco Tosello; Sara Abram; Ambra Fabbri; Alessandro Vairo; Dario Leone; Franco Veglio (Italian Journal of Medicine, 2013)
Introduction: Acute and chronic aortic syndromes are associated with substantial morbidity and mortality. Silent risk factors such as arterial hypertension and aortic root dilatation can increase the likelihood of aortic dissection or rupture. The relationship between arterial hypertension and the dimensions of the aortic root dimension is a topic of active debate. Materials and methods: We reviewed the literature on the physiopathology, diagnosis, natural history, and management of thoracic aortic aneurysms. Results: Biological variables influencing the size of the aorta include age, sex, body surface area, pressure values, and stroke volume. Pathologic enlargement of the thoracic aorta can be caused by genetic, degenerative, inflammatory, traumatic, or toxic factors. Studies investigating the correlation between aortic dimensions and arterial pressures (diastolic, systolic, or pulse) have produced discordant results. Discussion: Classically, emphasis has been placed on the importance of hypertension-related degeneration of the medial layer of the aortic wall, which leads to dilatation of the thoracic aorta, reduced aortic wall compliance, and increased pulse pressures. However, there are no published data that demonstrate unequivocally the existence of a pathogenetic correlation between arterial hypertension and aortic root dilatation. Furthermore, there is no evidence that antihypertensive therapy is effective in the management of nonsyndromic forms of aortic root dilatation. An interesting branch of research focuses on the importance of genetic predisposition in the pathogenesis of thoracic aortic aneurysms. Different genetic backgrounds could explain differences in the behaviour of aortic walls exposed to the same hemodynamic stress. Further study is needed to evaluate these focal physiopathological aspects.